2020
DOI: 10.37033/fjc.v5i2.154
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kandungan Mineral Pasir Pantai Bajul Mati Kabupaten Malang Menggunakan XRF dan XRD

Abstract: Mineral exploration in Indonesia has not been evenly distributed, so a study with title analysis of the sand mineral content of Bajul Mati Malang Regency was carried out using XRF and XRD. The aims of this study to determine the percentage of mineral that containing in the sand of Bajul Mati beach in Malang Regency. The instruments used XRF and XRD where the samples were placed in a sample holder and irradiated with X-rays then. The result of analysis of mineral content and metal oxide in Bajul Mati beach sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A study conducted by Sumari et al, 2020 concluded that the mineral content of the sand at Bajul Mati Beach, Malang Regency, is the highest, Silica (SiO2), and has the potential to be used as nano-silica material [4]. Verryon Harap and Mukti Hamjah Harahap, 2013, examined the characteristics of Labuhan Batu red sand using SEM test and X-ray diffraction, it was found that the sand has cavities on its surface and the most atoms contained are Si [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Sumari et al, 2020 concluded that the mineral content of the sand at Bajul Mati Beach, Malang Regency, is the highest, Silica (SiO2), and has the potential to be used as nano-silica material [4]. Verryon Harap and Mukti Hamjah Harahap, 2013, examined the characteristics of Labuhan Batu red sand using SEM test and X-ray diffraction, it was found that the sand has cavities on its surface and the most atoms contained are Si [5].…”
Section: Introductionmentioning
confidence: 99%